ANALISIS KELEMBAGAAN GAPOKTAN DALAM KEGIATAN LEMBAGA DISTRIBUSI PANGAN MASYARAKAT (LDPM) DI KABUPATEN GROBOGAN - Arip Wijianto; Widiyanto Widiyanto; Sapja Anantanyu (Universitas Sebelas Maret, 2015)
This research aims to explain in detail about the condition of Gapoktan institutional through activities of Reinforcement of Society Food’s Distributive Institution (Reinforcement-LDPM) at the Regency of Grobogan considered from superstructur aspect, community profiles of farmers the member of Gapoktan, and organizational profile aspect of the Gapoktan. Qualitative method and descriptive approach were used in this research. The sampling was snowball sampling technique. The technique of data collection used visceral interview, observation, and record-keeping. The tryout of data validity used triangulation source and triangulation method, whereas the data analysis used three main components, i.e. (1) data reduction, (2) data display, and (3) drawing conclusion and verification. Based on the research result, it can be concluded that analysis of Gapoktan institutional considered from superstructure aspects including government policy which influenced Gapoktan institutional. Both the federal government and local government of Grobogan Regency have issued some policies that support the reinforcement activities of Society Food’s Distributive Institution (LDPM), but the government policy about Bulog standardization was considered that it was too difficult for Gapoktan institutional. Considered from community profile, the development of Gapoktan institutional has transpired well enough because of having sufficient asset, collective action in both of routine meeting and directive counseling, drawing conclusion by the chief of Gapoktan through discussion and coordination focus, whereas the relationship between Gapoktan institutional with the other Gapoktan has transpired well. Considered from its institutional profile, the Gapoktan still had constraints or problem. Looking to its organization system, the structure of labor units of the reinforcement activities of Society Food’s Distributive Institution (LDPM) had not been organized well. The members prefer to profitable jobs than the voluntary Gapoktan. Outsides, the institutional management and resource allocation had not well complied.